Clinical features and treatment outcomes of otitis media with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (OMAAV): A retrospective analysis of 235 patients from a nationwide survey in Japan. Issue 1 (2nd January 2017) - Harabuchi, Yasuaki; Kishibe, Kan; Tateyama, Kaori; Morita, Yuka; Yoshida, Naohiro; Kunimoto, Yasuomi; Matsui, Takamichi; Sakaguchi, Hiroshi; Okada, Masahiro; Watanabe, Takeshi; Inagaki, Akira; Kobayashi, Shigeto; et al.
Abstract : Objective : We aimed to analyze clinical features and treatment outcomes of otitis media caused by antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), i.e. otitis media with AAV (OMAAV). Methods : This survey was performed between December 2013 and February 2014. The study began with a preliminary survey to 123 otolaryngology institutions in Japan to inquire about their experiences with OMAAV patients during the past 10 years, and was followed by a questionnaire survey to investigate clinical and laboratory findings. OMAAV was defined using the criteria described in the text. Results : Two hundred and thirty-five patients classified as OMAAV were enrolled in this study. They were characterized as follows: (1) disease onset with initial signs/symptoms due to intractable otitis media with effusion or granulation, which did not respond to ordinary treatments such as antibiotics and insertion of tympanic ventilation tubes, followed by progressive hearing loss; (2) predominantly female (73%) and older (median age: 68 years); (3) predominantly myeloperoxidase (MPO)-ANCA-positive (60%), followed by proteinase 3 (PR3)-ANCA-positive (19%) and both ANCAs-negative (16%); (4) frequently observed accompanying facial palsy (36%) and hypertrophic pachymeningitis (28%); and (5) disease often involving lung (35%) and kidney (26%) lesions. Four factors associated with OMAAV were found to be related to an unfavorable clinical course threatening the patient's hearing and/or lives, namely facial palsy, hypertrophic pachymeningitis, both ANCAs-negative phenotype, and disease relapse. The occurrence of hypertrophic pachymeningitis was associated with facial palsy ( p < 0.05), both ANCAs-negative phenotype ( p < 0.001), and headache ( p < 0.001). The administration of corticosteroid together with an immunosuppressant was an independent predicting factor for lack of disease relapse (odds ratio [OR] = 1.90, p = 0.03) and an improvement in hearing loss (OR =2.58, p = 0.0002). Conclusion : Since OMAAV has novel clinical features, the disease may be categorized as a subentity for the classification of AAV.